A constituição do pensamento crítico em tempos de informação e desinformação - Silva, Jessica Suellen Palmeira (2022)
Modern technology and connectivity present in our society makes access to information occur quickly and easily, but also generates the process of disinformation, which includes the dissemination of false information, known as fake news, from English. The information conveyed by the mainstream press doesthe job of informing what is at the center of information, at the heart of the economy; although they are fundamental in the process of fighting disinformation, they do not portray what happens in the outskirts of cities, therefore limiting themselves to a welfare and criminalist view on peripheral neighborhoods. In this sense, Mural Journalism Agency of the Periphery's mission is to minimize information gaps and contribute to the deconstruction of stereotypes created on the peripheries. Based on these questions and considering that education is one of the fundamental conditions for the development and constitution of the human being, the present research aims for the comprehension, through the interpretation of young participants from Mural Journalism Agency of the Periphery, of which factors are involved in the inconsistency between the access to information and acceptance of fake news. As specific objectives, we seek to understand the reason why, despite access to information, there are people who believe in fake news, by means of empirical research, establishing theoretical mediations based on historical-dialectical materialism, from the historical-cultural psychology contributions and formulations and studies by Paulo Freire. As an attempt to approach the determining factors of the acceptance of false news, there is a pursuit of subsidizing and strengthening intervention actions with the objective of contributing for the constitution of critical thinking. For this purpose, this research adopted questionnaires with identification questions and in-depth interviews with Mural’s young journalists as data collection procedure, and content analysis as analysis procedure. Participants have shown that, as readers, they access a variety of media vehicles and are concerned about being aware of its origin and reputability, while also being aware of the production of misinformation and the means to fight it. Finally, we consider that it is necessary to create strategies for dialogical and media education, which are examples of actions that aim at the constitution of critical thinking information and disinformation times. Education is the base and dialogue is fundamental for learning, with media education being a concrete mediation in the construction of critical thinking that seeks to intentionally reveal reality